Application of didactic resources in the teaching learning process of the English Language for students of first and second year of Bachillerato of Colegio Fiscal Técnico Dr. Juan Henríquez Coello, in Machala City, academic year 2014-2015. - Mizhquiri Manzano, Eliana Belén; Reyes Suriaga, Jéssica Dolores; Rojas Bravo, Jenny María (My University, 2015)
El fenómeno de la globalización ha contribuido de gran manera a convertir al inglés en el idioma más importante y necesario de la actualidad, siendo entendido el idioma de los países desarrollados, teniendo un alto índice de crecimiento alrededor del mundo.
The phenomenon of globalization has contributed greatly to make English the most important and necessary language currently being understood language developed countries, with high rates of growth worldwide.
Keywords: APPLICATION; RESOURCE; LEARNING; LANGUAGE